The effect of alcohol on the rate and degree of orthodontic tooth movement in guinea pigs - Dacuyan, Wilfredo Jr., T.
The present study examined the effect of alcohol on the rate and degree of orthodontic tooth movement in guinea pigs. Fifteen adult male guinea pigs were randomly assigned and distributed into the three groups -LD (10% ETOH), HD (20% ETOH) and Control. The experimental groups received oral administration of their corresponding dosages at 2.5 g/kg for 21 days, starting on the day of the installation of orthodontic appliance. Direct linear measurements of tooth separation were recorded on days 7, 14 and 21. After data collection, one guinea pig from each group was euthanized for histologic study of the periodontium surrounding the left maxillary incisor.